2017
DOI: 10.1111/jfbc.12378
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and bovine plasma oxidation-inhibitory activities of spent hen meat protein hydrolysates

Abstract: Hydrolysis of spent hen meat proteins with pepsin and pepsin 1 pancreatin yielded SPH-P and SPH-PPc hydrolysates, respectively. The hydrolysates dose-dependently inhibited activities of human recombinant renin (IC 50 0.34 and 0.52 mg/mL, respectively) and angiotensin I-converting enzyme (ACE, IC 50 0.64 and 0.42 mg/mL, respectively). The hydrolysates had lower cysteine and tryptophan contents but similar contents of other amino acids when compared with the parent spent hen protein isolate. SPH-P, but not SPH-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…Then, these peptides were rapidly metabolized into inactive products leading to the subsequent reduction in activity, especially for 85 mg/kg bw Hpp11, with no apparent antihypertensive by 8 h post-administration. A similar antihypertensive pattern was recently described by Udenigwe et al using by-product hen meat protein hydrolysates [ 43 ]. These results showed that at relatively low doses, Hpp11 was able to reduce the SBP in the same manner as Captopril, demonstrating its potential applicability in HTN treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Then, these peptides were rapidly metabolized into inactive products leading to the subsequent reduction in activity, especially for 85 mg/kg bw Hpp11, with no apparent antihypertensive by 8 h post-administration. A similar antihypertensive pattern was recently described by Udenigwe et al using by-product hen meat protein hydrolysates [ 43 ]. These results showed that at relatively low doses, Hpp11 was able to reduce the SBP in the same manner as Captopril, demonstrating its potential applicability in HTN treatment.…”
Section: Discussionsupporting
confidence: 79%
“…The extracted proteins in this study contained mainly myofibrillar proteins as reported previously [ 29 , 30 ]. The major protein bands include myosin heavy chain (~220 kDa), actin (42 kDa), and myosin light chain (15–25 kDa) ( Figure 1 A) [ 37 , 55 , 56 ]. These proteins were cleaved into peptides below 10 kDa after the hydrolysis and more than half of peptides were below 3 kDa ( Figure 1 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, finding a more sustainable solution for spent hen utilization which also yields additional value to the egg industry is highly relevant. Previous work on spent hens has mainly included extraction and characterization of spent hen proteins [ 28 , 30 ], fabrication of nanomaterials [ 30 , 31 , 32 ], and preparation of bioactive peptides [ 29 , 33 , 34 , 35 , 36 , 37 ]. We have previously prepared a spent hen muscle protein hydrolysate (SPH) that exhibited anti-inflammatory activity in young rodents [ 34 ]; a few anti-inflammatory peptides have been identified therein [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the extraction methods of target compounds from these types of materials more attention must be payed to other details, than in the case of plant-based materials, due to their complex matrix and the possibility to obtain more diversified categories of wastes (skin, blood, shells, etc.). Most of the studies describes a combination of thermal, mechanical, chemical and enzymatic methods, such as blending followed by extraction with alkali/acid and hydrolysis with pepsin/pancreatin for the obtaining of peptides from spent hen meat hydrolysate [134] or homogenization followed by enzymatic hydrolysis [135], homogenization, hydrolysis, and ultrafiltration for obtaining carnosine from chicken meat [136].…”
Section: Recovery Of Antioxidants From Agro-industrial Side Streamsmentioning
confidence: 99%